2015
DOI: 10.1007/s00203-015-1146-8
|View full text |Cite
|
Sign up to set email alerts
|

ERG11 mutations and expression of resistance genes in fluconazole-resistant Candida albicans isolates

Abstract: Azole resistance in the pathogenic yeast Candida albicans poses significant challenges for its antibiotic treatment. The conformational change of the target enzyme 14 alpha-demethylase (Erg11p) due to ERG11 gene mutations is one of the mechanisms resulting in the azole resistance. ERG11 of 23 isolates (8 susceptible and 15 resistant) and 6 standard strains of Candida albicans were amplified and sequenced. Nineteen missense mutations were detected. Two mutations, G487T (A114S) and T916C (Y257H), coexisted exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 25 publications
1
22
0
1
Order By: Relevance
“…Surprisingly, in spite of using the same clonal genetic background of strain E11ura3Δ5=, RT-qPCR assays showed variations in amounts of ERG11 mRNA detected, possibly due to different mRNA half-lives within the cell or to slight variations of UPC2 expression, the transcription factor that regulates ERG11 (29). However, the variations detected, less than 3-fold, are not expected to have a significant effect on fluconazole MIC or to be correlated to a specific resistance pattern, as previously reported in several studies with C. albicans (30,31,32,33). Furthermore, both the Y132H and G464S CaERG11 alleles were expressed at the same level in C. lusitaniae E11ura3Δ5=, indicating that the lack of phenotype with Y132H only was probably not derived from a decreased expression level of CaERG11.…”
Section: Discussionsupporting
confidence: 72%
“…Surprisingly, in spite of using the same clonal genetic background of strain E11ura3Δ5=, RT-qPCR assays showed variations in amounts of ERG11 mRNA detected, possibly due to different mRNA half-lives within the cell or to slight variations of UPC2 expression, the transcription factor that regulates ERG11 (29). However, the variations detected, less than 3-fold, are not expected to have a significant effect on fluconazole MIC or to be correlated to a specific resistance pattern, as previously reported in several studies with C. albicans (30,31,32,33). Furthermore, both the Y132H and G464S CaERG11 alleles were expressed at the same level in C. lusitaniae E11ura3Δ5=, indicating that the lack of phenotype with Y132H only was probably not derived from a decreased expression level of CaERG11.…”
Section: Discussionsupporting
confidence: 72%
“…of them, 2 mutations, G487T (A114S) and T916C (Y257H), coexisted solely in 14 fluconazole -resistant separate. To know the resisting device in the separate with G487T and T916C mutations, we contrast the explanation of 5 resisting -relevant genes in the 14 azole -resisting separate with those in the sensitive kind race ATCC 10231, Saccharomyces cerevisiae AD/CDR1, and AD/CDR2 (24). The results of this study indicated that extracts of T. polium and C. colocynthis, especially C. colocynthis extract, collected from Sistan region, showed good antimicrobial activity against Candida albi-…”
Section: Discussionmentioning
confidence: 84%
“…2a). Point mutations in ERG11 and ERG3 were found in most isolates, although only 2 isolates had mutations in ERG11, which has been reported to confer resistance (15,28,29). The remaining mutations were also previously described in fluconazole-susceptible isolates and do not seem to play a major role in resistance (15,(30)(31)(32).…”
mentioning
confidence: 78%